2015
DOI: 10.1242/dev.104927
|View full text |Cite
|
Sign up to set email alerts
|

Thalamic afferents influence cortical progenitors via ephrin A5-EphA4 interactions

Abstract: The phenotype of excitatory cerebral cortex neurons is specified at the progenitor level, orchestrated by various intrinsic and extrinsic factors. Here, we provide evidence for a subcortical contribution to cortical progenitor regulation by thalamic axons via ephrin A5-EphA4 interactions. Ephrin A5 is expressed by thalamic axons and represents a high-affinity ligand for EphA4 receptors detected in cortical precursors. Recombinant ephrin A5-Fc protein, as well as ephrin A ligand-expressing, thalamic axons affec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
26
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
3
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(29 citation statements)
references
References 75 publications
1
26
1
Order By: Relevance
“…These observations are consistent with our previous findings that inactivation of EphA5, a receptor of ephrin-A5, also reduced inter-male aggression [23], suggesting that ephrin-A5/EphA5 signaling modulates neural pathways in brain regions that control aggression. Ephrin-A5 has been shown to regulate neural progenitor cell production [67], interneuron migration [68] and neuronal dendritic arborization [69]. Future studies will reveal which specific functions are required for the regulation of aggressive behavior.…”
Section: Discussionmentioning
confidence: 99%
“…These observations are consistent with our previous findings that inactivation of EphA5, a receptor of ephrin-A5, also reduced inter-male aggression [23], suggesting that ephrin-A5/EphA5 signaling modulates neural pathways in brain regions that control aggression. Ephrin-A5 has been shown to regulate neural progenitor cell production [67], interneuron migration [68] and neuronal dendritic arborization [69]. Future studies will reveal which specific functions are required for the regulation of aggressive behavior.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, it is possible that the decreased maternal behavior seen in the null mice is due to alteration in the mesolimbic DA system. However, since ephrin-A5 is expressed broadly in the brain (Deschamps et al , 2009, Gao et al , 1998), and has been shown to regulate neurogenesis (Depaepe et al , 2005, Gerstmann et al , 2015, Noh & Park, 2015, Shu et al , 2016), and formation of several other neural circuits (Carvalho et al , 2006, Guellmar et al , 2009, Steinecke et al , 2014, Tadesse et al , 2013, Yates et al , 2014) the precise mechanism underlying maternal care deficiency remains to be determined by future investigations. Thus, the mechanistic connection of ephrin-A5 function to maternal behavior is at present unclear, and this gene may not regulate maternal care exclusively.…”
Section: Discussionmentioning
confidence: 99%
“…The most extensively investigated have been EphA4 , EphA7 , EphrinA2 ( Efna2 ) and EphrinA5 ( Efna5 ). Roles for these genes have been demonstrated in parcellation of thalamic nuclei [19], target selection and topography of retinal axons into the thalamus [40], topographic guidance of thalamic axons through the ventral telencephalon [41], areal and layer-specific targeting and topography (reviewed in [42]), reciprocal corticothalamic axon guidance and target selection [43, 44] and even influences on cortical progenitor proliferation and differentiation dynamics [45]. EphB1 and - B2 have also recently been shown to mediate thalamic axon guidance through the ventral telencephalon [46].…”
Section: Resultsmentioning
confidence: 99%